Disaster Risk Reduction and Emergency Preparedness for Children With Autism in Facing Earthquake Disaster in Yogyakarta - Fika Nur Indriasari; Prima Daniyati K; Linda Widyarani (Universitas Muhammadiyah Yogyakarta, 2018)
Special Needs Children (ABK) is one of the vulnerable groups in times of disaster. Some of them have mobility hindrance even to perform a defence and personal escape independently, therefore, information is needed on what procedures or plans to take to rescue ABKs who need help from people around them (e.g. teachers, classmates, school staffs). Objectives: To determine the preparedness of children with special needs in dealing with earthquake disasters in Yogyakarta. This research uses a observational descriptive design. The samples are selected using a purposive sampling technique, while the data are collected by means of observation sheets. The respondents for this research are special needs children with autism at ‘SLB N Pembina’, Yogyakarta. Data analysis is performed using a descriptive qualitative analysis. Disaster awareness trainings give a positive influence in reducing disaster risks and in increasing the disaster preparedness of special needs children with autism. Special needs children with autism show ability and participation after performing 5 times simulation. The preparedness increase of special needs children after training is 39%.